Copper-Catalyzed Synthesis of Dibenzo[b,f]imidazo[1,2-d][1,4]oxazepine Derivatives via a Double Ullmann Coupling Reaction - Chen, Xin-Yi; Li, Zhuo-Huan; Liu, Jian-Quan; Wang, Xiang-Shan (Synthesis, 2019)
A double Ullmann coupling reaction successfully takes place between 4,5-diaryl-2-(2-bromophenyl)-1H-imidazoles and 2-bromophenols in the presence of Cs2CO3. This procedure is catalyzed by copper(I) iodide and o-phenanthroline and provides an efficient method for the synthesis of dibenzo[b,f]imidazo[1,2-d][1,4]oxazepine derivatives in good yields.
Keywords: Ullmann coupling; dibenzoimidazo[1,4]oxazepines; copper(I) iodide; o-phenanthroline; catalysis